Successful treatment of cytomegalovirus pneumonia in a child on maintenance chemotherapy for acute lymphoblastic leukemia without the use of intravenous immunoglobulin - Sidharth Totadri, MD, DM; Venkatraman Radhakrishnan, MD, DM (Elsevier, 2017)
Cytomegalovirus (CMV) infection is seldom suspected in children receiving chemotherapy for hematological malignancies. However, in populous countries such as India, incidence and subsequent re-activation during immunosuppression may be greater than anticipated. CMV disease can manifest in children with acute lymphoblastic leukemia with chorioretinitis, pneumonia, prolonged cytopenia, enterocolitis and fever unresponsive to antibiotics. We describe our experience in managing a child with acute lymphoblastic leukemia who presented during maintenance therapy with CMV pneumonia. She was successfully treated with ganciclovir alone. Although intravenous immunoglobulin is recommended as adjunctive therapy, its use may be restricted in resource limited settings.